Assessment of reproductive capacity in females of Smith, 1869 (Brachyura, Portunoidea) during a period of high reproductive activity - Antunes, Mariana [UNESP]; Fransozo, Vivian [UNESP]; Castilho, Antonio Leão [UNESP]; José Cobo, Valter [UNESP]; Teixeira, Gustavo Monteiro [UNESP]; Fransozo, Adilson [UNESP] (Taylor & Francis, 2014)
The reproductive capacity of the swimming crab Callinectes danae Smith, 1869 was assessed based on the reproductive investment (RI) of ovigerous females and the gonadosomatic index (GI) of non-ovigerous adult females. Crabs were collected in June 2009 with a shrimp fishing boat at Ubatuba (23° 26′S 45° 02′W) São Paulo, Brazil. Overall, 191 adult females were analyzed, of which 108 were ovigerous and 83 non-ovigerous. The size of ovigerous females ranged from 54.5 to 79.8 mm carapace width (CW) and non-ovigerous females ranged from 56.0 to 80.9 mm CW. RI values did not differ among the size classes (ANOVA, p > 0.05), with an overall mean of 15.8%. The same occurred with the Gonadossomatic index for non-ovigerous females, for which the mean value was 11.7%. The regression between the dry weight of the egg mass and the dry weight of the crab (Student’s t, p = 0.25; ttab = 1.66; tcal = 0.66) indicated an isometric relationship for the variables analyzed. The simultaneous occurrence of gonadal maturation and embryonic development in ovigerous females suggests that these crabs may spawn at least twice in the same breeding season and reveals the need for evaluation of the allocation of energy in subsequent spawns.
Keywords: Gonads; Multiple spawnings; Embryonic development; Fecundity